Productivity Of Capsicum Annuum Under Grewia Optiva-Based Traditional Agroforestry System In Mid Hill Zone Of Himachal Pradesh (India) (Applied Biological Research, 2020)
Agroforestry is relatively a new name for a set of old practices. The  multifarious trees deliberately retained by the farmers on the farm bund  form the agroforestry combinations, which supplement the fodder, fuel,  fiber, fruits and flosses as their life support system. Grewia optiva is an  important fodder tree retained on farm bunds by farmers in Western  Himalayan region. The present investigation was aimed to study the effect  of G. optiva based traditional agroforestry system i.e. agri-silviculture, on  the productivity of bell pepper (Capsicum annuum). The crown spread of  tree was considered major factor and categorized into different classes for  quantifying its effect on crop growth and production along radial transects  from tree trunk. Results revealed that the crown classes significantly  affected the yield of bell pepper causing about 33% reduction in yield under  tree canopy as compared to the open condition.
Keywords: Agroforestry; bell pepper; productivity; Grewia optiva; crown spread